2017
DOI: 10.1186/s12887-017-0844-6
|View full text |Cite|
|
Sign up to set email alerts
|

Validity of anthropometric equations to estimate infant fat mass at birth and in early infancy

Abstract: BackgroundIn newborns and children, body fat estimation equations are often used at different ages than the age used to develop the equations. Limited validation studies exist for newborn body fat estimation equations at birth or later in infancy. The study purpose was to validate 4 newborn fat mass (FM) estimation equations in comparison to FM measured by air displacement plethysmography (ADP; the Pea Pod) at birth and 3 months.MethodsNinety-five newborns (1–3 days) had their body composition measured by ADP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 44 publications
(67 reference statements)
1
39
0
Order By: Relevance
“…Body fat mass was determined according to the following validated equation: Fat mass = 1000 (0.39055 (birth weight [grams]/1000) + 0.0453 (flank skinfold (mm) − 0.03237 (length [cm]) + 0.54657. Four neonates had negative fat mass according to the equation, and a fat mass of zero grams was substituted.…”
Section: Methodsmentioning
confidence: 99%
“…Body fat mass was determined according to the following validated equation: Fat mass = 1000 (0.39055 (birth weight [grams]/1000) + 0.0453 (flank skinfold (mm) − 0.03237 (length [cm]) + 0.54657. Four neonates had negative fat mass according to the equation, and a fat mass of zero grams was substituted.…”
Section: Methodsmentioning
confidence: 99%
“…Especially, postnatal growth restriction of extremely preterm infants still remains a big challenge worldwide and is associated with an impaired neurodevelopmental outcome (2,3). Evaluation of the body composition and especially fat mass (FM) gain seems to be more accurate to evaluate the nutritional status in comparison to anthropometric parameters including Z-scores (4,5). The optimal body composition and reference values in ex premature infants at term-equivalent age are still unknown (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…The use of skinfold thickness to estimate FM is commonly used to circumvent the limitations of the aforementioned techniques, however; their use in infants is controversial, and the use of the correct prediction equations that account for ethnicity and age of the source population is essential in order to gain accurate estimates . Several studies have demonstrated low concordance in FM estimation between skinfold thickness and gold standard body composition measurements . This leaves a significant gap in body composition assessment during a critical window of growth that is important for understanding the development of obesity in research settings.…”
Section: Introductionmentioning
confidence: 99%